Hierarchical 3D Oxygenated Cobalt Molybdenum Selenide Nanosheets as Robust Trifunctional Catalyst for Water Splitting and Zinc–Air Batteries. Issue 19 (20th April 2020) - Prabhakaran, Sampath; Balamurugan, Jayaraman; Kim, Nam Hoon; Lee, Joong Hee
Abstract: The development of hierarchical nanostructures with highly active and durable multifunctional catalysts has a new significance in the context of new energy technologies of water splitting and metal–air batteries. Herein, a strategy is demonstrated to construct a 3D hierarchical oxygenated cobalt molybdenum selenide (O‐Co1− x Mo x Se2 ) series with attractive nanoarchitectures, which are fabricated by a simple and cost‐effective hydrothermal process followed by an exclusive ion‐exchange process. Owing to its highly electroactive sites with numerous nanoporous networks and plentiful oxygen vacancies, the optimal O‐Co0.5 Mo0.5 Se2 could catalyze the hydrogen evolution reaction and oxygen evolution reaction effectively with a low overpotential of ≈102 and 189 mV, at a current density of 10 mA cm −2, respectively, and exceptional durability. Most importantly, the O‐Co0.5 Mo0.5 Se2 ||O‐Co0.5 Mo0.5 Se2 water splitting device only entails a voltage of ≈1.53 V at a current density of 10 mA cm −2, which is much better than benchmark Pt/C||RuO2 (≈1.56 V). Furthermore, O‐Co0.5 Mo0.5 Se2 air cathode‐based zinc–air batteries exhibit an excellent power density of 120.28 mW cm −2 and exceptional cycling stability for 60 h, superior to those of state‐of‐art Pt/C+RuO2 pair‐based zinc–air batteries. The present study provides a strategy to design hierarchical 3D oxygenated bimetallic selenide‐based multifunctional catalysts for energy conversion and storage systems. Abstract : The present investigation demonstrates an approach for the fabrication of oxygenated Co0.5 Mo0.5 Se2 nanosheets (NSs). The water splitting device achieves a cell voltage of 1.53 V at 10 mA cm −2, outperforming the benchmark Pt/C||RuO2 device (≈1.56 V). Most specifically, as an air cathode, O‐Co0.5 Mo0.5 Se2 NSs show high specific capacity, excellent energy/power densities, and an ultralong round trip efficiency for 60 h.